Pseudo tumor tuberculosis of the uterine cervix: about a case at the colposcopy and cervico vaginal pathologies unit of the University hospital Le Dantec, Dakar, Senegal - Gassama, Omar; Dieme, Marie Edouard Faye; Diallo, Moussa; Niang, Mouhamadou Mansour; Diouf, Abdoul Aziz; Gueye, Mamour; Ndiaye, Abdou; Diouf, Alassane; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Tuberculosis is still common in developing countries and particularly in sub-Saharan Africa since the advent of the HIV/AIDS. Genital tuberculosis usually affects young women in genital activity period. The most frequent locations are tubal, endometrial and ovarian. The cervical location is rare. We report on the case of a 36 years old patient with eight pregnancies and eight deliveries who lives in a rural area and has got in her history 8 vaginal deliveries with four living children and 4 dead children and who was referred by a colleague for a "tumor of the uterine cervix". In her medical history, there was a BCG vaccination during childhood and she had never received Pap smear. The colposcopy revealed an ulcerating budding tumor of the cervix with necrotic areas. The colposcopy biopsy revealed fibrocaseous tuberculosis of the uterine cervix. Tuberculosis is still a common disease in developing countries. The cervical localization is rare but should be considered in case of an ulcerating tumor budding of the cervix.